COMPLIANCE OF TAKING ANTI-TUBERCULOSIS DRUGS IN TUBERCULOSIS PATIENTS AT SEVERAL PUSKESMAS IN SLEMAN REGENCY, YOGYAKARTA - Sindy Cisna Ambarwati; Dyah Aryani Perwitasari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Tuberculosis is a widespread disease listed from the top 10 triggers of death in the world (ranked above HIV/AIDS. According to the Sleman Health Office, the number of TB services at the Sleman regional health center in 2019 was 5466 cases with the cure rate for pulmonary TB with positive smear is 87 ,88%. After a person is diagnosed with Tuberculosis, it will be continued with TB treatment for 6 months, this makes the patient bored and does not comply with taking medication. Based on previous research, it was found that the adherence rate in patients undergoing treatment was 72.7%. Considering that TB is an infectious disease so that adherence to pulmonary TB treatment is important to analyze, this study aims to determine the level of adherence to taking anti-tuberculosis drugs in TB patients in several Puskesmas in Sleman area. Patients compliance was measured by MARS. This study used a descriptive observational design applying the cross-sectional design. The subjects were pulmonary TB patients registered as TB sufferers based on secondary data at the Sleman District Health Office, aged 15-70 years old, seeking treatment in March-April 2020, receiving treatment undergoing OAT therapy category 1 for at least one month and willing to be respondents. The results of the study revealed that 54% were male and 46% were female, dominated by 62% aged >25 years of 13 subjects. The score of MARS questionnaire obtained was <25. The results of the study concluded that the patient complied with 60.82% and the non-adherent patient was 39.19%.